Peningkatan kualitas literasi qur’ani melalui kegiatan pembelajaran bt al-qur’an di tpq remaja masjid jami’ gresik - Murtadho, Muchammad Zainul (Maliki Interdisciplinary Journal, 2025)
This study aims to describe the improvement of the quality of Qur’anic literacy of students at the TPQ Remaja Masjid Jami’ Gresik through the implementation of the Al-Qur’an Reading and Writing (BT Al-Qur’an) learning activities. The quality of Qur’anic literacy in this study was measured based on the ability to read hijaiyah letters, pronounce letters and harakat correctly, and write verses of the Qur’an simply. The research method used was descriptive qualitative with data collection through observation, interviews, and documentation. The results of the study showed that structured and sustainable BT Al-Qur’an learning activities had a positive impact on improving the Qur’anic literacy skills of students. Students showed a significant increase in the recognition of hijaiyah letters, accuracy of pronunciation, and the ability to write simple verses. Supporting factors for the success of this activity include interactive teaching methods, the use of interesting learning media, and active support from ustadz and TPQ administrators. This study implies the importance of implementing a systematic BT Al-Qur’an program in improving the quality of understanding and practice of the Qur’an from an early age.